K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 8 2016

\(1,x^2+5x-6=x^2-x+6x-6=x\left(x-1\right)+6\left(x-1\right)=\left(x-1\right)\left(x+6\right)\)

\(3,7x-6x^2-2=-6x^2+7x-2=-6x^2+3x+4x-2=3x\left(-2x+1\right)+2\left(2x-1\right)\)

\(=3x\left(1-2x\right)-2\left(1-2x\right)=\left(1-2x\right)\left(3x-2\right)\)

\(2,5x^2+5xy-x-y=5x\left(x+y\right)-\left(x+y\right)=\left(x+y\right)\left(5x-1\right)\)

14 tháng 10 2018

= (4y)^2 + 12ax - (3x)^2 - (2a)^2

= (4y-3x)^2 - (2a)^2

= (4y-3x-2a)(4y-3x+2a) 

14 tháng 8 2015

a/ \(=3y^2-6y-2x+1\)

b/ \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

c/ \(=\left(2-x\right)^3\)

d/ \(=xy^2+x^2y+3xy+x^2y+x^3+3x^2-3xy-3x^2-9x\)

\(=xy\left(y+x+3\right)+x^2\left(y+x+3\right)-3x\left(y+x+3\right)\)

\(=\left(xy+x^2-3x\right)\left(y+x+3\right)=x\left(y+x-3\right)\left(y+x+3\right)\)

e/ \(=xy-x^2+2x-y^2+xy-2y\)

\(=x\left(y-x+2\right)-y\left(y-x+2\right)=\left(x-y\right)\left(y-x+2\right)\)

14 tháng 8 2015

a) =(2x+3y-1)2

b)=-(x-1)3

c)=-(x3-6x2+12x-8)=-(x-2)3

d)x3 + 2x2y + xy2 – 9x

    = x(x2 + 2xy + y2 -9)

    = x[(x2 + 2xy + y2) - 32]

    = x[(x + y)2 - 32]

    = x (x + y – 3)(x + y + 3)

e) 2x-2y-x2+2xy-y2=2(x-y)-(x-y)2=(x-y)(2-x+y)

11 tháng 7 2016

\(=x\left(x^2-2x+1-y^2\right)\)

\(=x\left(\left(x-1\right)^2-y^2\right)\)

\(=x\left(x-1-y\right)\left(x-1+y\right)\)

11 tháng 7 2016

bài này bn hoc qt đung rui, tui làm nhé

1)= x(x2 -2x +1 - y) = x((x-1)2 - y)

11 tháng 7 2016

1/ \(3x^2+6x+3-3y^2=3x^2+3x+3x+3-3y^2\)

\(=3\left(x^2+2x+1-y^2\right)\)

\(=3\left[\left(x^2+2x+1\right)-y^2\right]\)

\(=3\left[\left(x+1\right)^2-y^2\right]\)

\(=3\left(x+1-y\right)\left(x+1+y\right)\)

2/ \(25-x^2-y^2+2xy=5^2-\left(x^2+y^2-2xy\right)\)

\(=5^2-\left(x-y\right)^2\)

\(=\left[5-\left(x-y\right)\right]\left(5+x+y\right)\)

\(=\left(5-x+y\right)\left(5+x+y\right)\)

3/ \(3x-3y-x^2+2xy-y^2=3\left(x-y\right)-\left(x^2-2xy+y^2\right)\)

\(=3\left(x-y\right)-\left(x-y\right)^2\)

\(=\left(x-y\right)\left[3-\left(x-y\right)\right]\)

\(=\left(x-y\right)\left(3-x+y\right)\)

17 tháng 8 2016

\(x^3-x^2-x+1\)

\(=x^2\left(x-1\right)-\left(x-1\right)\)  

\(=\left(x-1\right)\left(x^2-1\right)\)

29 tháng 9 2018

\(x^3-2x^2+x\)

\(=x\left(x^2-2x+1\right)\)

\(=x\left(x-1\right)^2\)

hk tốt

^^

29 tháng 9 2018

\(x^3-2x^2+x\)

\(=x\left(x^2-2x+1\right)\)

\(=x\left(x-1\right)^2\)

hk tốt

^^